Pengaruh Rendaman Air Hujan Di Samarinda Terhadap Aspal (AC-WC) Pada Pengujian Marshall - Ulwiyah Wahdah Mufassirin Liana; Adde Currie Siregar; Johanes Wicaksono (Jurnal Teknik Sipil Unaya, 2023)
Road pavement construction in Samarinda uses flexible pavement, in addition to the smoother surface, flexible pavement is easier to repair and the manufacturing time is faster, but it was continuously used and the weather was constantly changing the bending pavement must always be paid attention. The purpose of this study is to determine the optimum level of asphalt obtained when submerged in rainwater and analyze the effect of rainwater soaking on the marshall test. The asphalt content used in this study was 4%, 4.5%, 5.5%, and 6%. From the results of the studies that have been carried out, it can be concluded that test objects soaked using rainwater can affect the compressive strength of asphalt in marshall testing. At 1-day immersion, that was a decrease the stability is 8.15%, a decrease in the flow is 16.59%, VIM and VMA are increase 92.01% and 23.9%, VFWA was decrease 22.72%, while density is decrease 4.48% with MQ is increase 12.47%. In the 3-day immersion, that is increase stability by 4.70% and flow is increase17.96%, VIM and VMA are increase 24.67% and 9,44%, while VFWA is decrease 12.47%, density have decrease 2.19% and MQ neither decrease 13.06%.